TYPOLOGY OF CULTURES - Saitxanova Dinara Ruslanovna; Xonboboyeva Shoira; O’razova Dildora (TADQIQOTLAR, 2026)
Abstract Article explores the concept of cultural typology, which categorizes cultures based on various criteria such as values, norms, practices, and social structures. It examines different frameworks for understanding cultural differences, including Edward T. Hall’s high-context and low-context cultures, Geert Hofstede’s cultural dimensions theory, and Fons Trompenaars’ model of national culture differences. The article also discusses the implications of cultural typology for intercultural communication, globalization, and international business. By analyzing how cultures can be classified and compared, the article aims to provide insights into the complexities of cultural interactions in an increasingly interconnected world.